The Role of Exploration E-WOM to Improve Purchasing Decision for Online Retail Insurance Products in Indonesia - Abdullah, Syukur; Diposumarto, Ngadino Surip; Muharam, Hari (Research Horizon, 2025)
In the digital era, E-WOM has become an important factor influencing consumer behaviour, especially for high-risk products such as insurance. This study aims to explores the role of Electronic Word of Mouth (E-WOM) in increasing the purchase decision of bold retail insurance products in Indonesia. Using a survey method, this study uses a qualitative approach involving respondents from various digital platforms. Data analysis was carried out using statistical techniques to test the effect of source credibility, message content, media, and social interaction in E-WOM on purchasing decisions. The results show that the credibility of information sources, such as real user reviews and trusted influencers, has a positive effect on consumer trust and purchase intentions. Informative message content can reduce risk perception, while social media and marketplaces serve as the main channels for E-WOM. Social interaction through discussion strengthens trust and clarifies product information. This study contributes to the digital marketing strategy of retail insurance in Indonesia, with practical implications that insurance companies need to improve source credibility and message quality and maximize social interaction on digital platforms to encourage more effective purchasing decisions.